2008
DOI: 10.1007/s10462-009-9147-0
|View full text |Cite
|
Sign up to set email alerts
|

A formal logic approach to firewall packet filtering analysis and generation

Abstract: Recent years have seen a significant increase in the usage of computers and their capabilities to communicate with each other. With this has come the need for more security and firewalls have proved themselves an important piece of the overall architecture, as the body of rules they implement actually realises the security policy of their owners. Unfortunately, there is little help for their administrators to understand the actual meaning of the firewall rules. This work shows that formal logic is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Creating a visual representation of the connections between switches and routers is a common step in any structure analysis process. Topological interconnection represented by formal graphs is also often necessary for research in the domains of network modeling [32], [48] or attack graph generation [49], [37]. "A connection" between two switches, for example, is represented as a property chain between two individuals of the managed network component concept in the IO (see Listing 2).…”
Section: Io Use Casesmentioning
confidence: 99%
“…Creating a visual representation of the connections between switches and routers is a common step in any structure analysis process. Topological interconnection represented by formal graphs is also often necessary for research in the domains of network modeling [32], [48] or attack graph generation [49], [37]. "A connection" between two switches, for example, is represented as a property chain between two individuals of the managed network component concept in the IO (see Listing 2).…”
Section: Io Use Casesmentioning
confidence: 99%
“…The first works ( [2], [25], [13]) proposed firewall management methodologies which could be exclusively applied to networks where any security function was a hardware appliance. Later, formal verification techniques have been exploited to provide correctness assurance after the automated computation of firewall configurations ( [12], [5], [17], [22], [1]). Then, after the advent of softwarization in networking, this research path has found new relevance ( [20], [8], [9], [6]) and currently has become an important research trend in network security.…”
Section: Related Workmentioning
confidence: 99%
“…However, all these three works exclusively target traditional networks, and do not offer either optimality or formal verification. Formal mathematical models have been, instead, presented in [14] and [15], where formal methodologies are used to automatically compute firewall configuration. However, in both cases these techniques work only in specific cases, not related to virtualized networks: [14] follows the syntax of IPChains and Cisco's PIX, whereas [15]'s technique has been validated only with SCADA-firewall configuration.…”
Section: Related Workmentioning
confidence: 99%